Rejuvenating Medical Education - Marshall, Robert,Bleakley, Alan (Cambridge Scholars Publisher, 2017)
Returning to Homer's Iliad and Odyssey for inspiration, this book uses these epics as a medium through which we might think imaginatively about key issues in contemporary medicine and medical education. These issues include doctors as heroes, and the legacy of heroic medicine in an age of clinical teamwork, collaboration and a more feminine medicine. The authors challenge ingrained habits in medical education, such as the way we characteristically
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Medicine in literature